Are Repeated Single-Limb Heel Raises and Manual Muscle Testing Associated With Peak Plantar-Flexor Force in People With Inclusion Body Myositis?. Issue 4 (1st April 2014) - Harris-Love, Michael O.; Shrader, Joseph A.; Davenport, Todd E.; Joe, Galen; Rakocevic, Goran; McElroy, Beverly; Dalakas, Marinos
Abstract : Background: Repeated heel raises have been proposed as a method of ankle plantar-flexor strength testing that circumvents the limitations of manual muscle testing (MMT). Objective: The study objective was to examine the relationships among ankle plantar-flexion isometric maximum voluntary contraction (MVC), repeated single-limb heel raises (SLHRs), and MMT in people with myositis. Design: This was a cross-sectional study with a between-group design. The ability to complete 1 SLHR determined group assignment (SLHR group, n=24; no-SLHR group, n=19). Methods: Forty-three participants with myositis (13 women; median age=64.9 years) participated. Outcome measures included MVC, predicted MVC, Kendall MMT, and Daniels-Worthingham MMT. Results: The Kendall MMT was unable to detect significant ankle plantar-flexor weakness established by quantitative methods and was unable to discriminate between participants who could and those who could not perform the SLHR task. Ankle plantar-flexion MVC was not associated with the number of heel-raise repetitions in the SLHR group (pseudo R 2 =.13). No significant relationship was observed between MVC values and MMT grades in the SLHR and no-SLHR groups. However, a moderate relationship between MVC values and MMT grades was evident in a combined-group analysis (ρ=.50–.67). Limitations: The lower half of both MMT grading scales was not represented in the study despite the profound weakness of the participants. Conclusions: Both Kendall MMT and Daniels-Worthingham MMT had limited utility in the assessment of ankle plantar-flexor strength. Repeated SLHRs should not be used as a proxy measure of ankle plantar-flexion MVC in people with myositis.